Review of Structural Performance and Repair Strategies for Fire-Damaged Reinforced Concrete Beams - Noor, Deliar; Gunadi, Riawan (Jurnal Teknik Sipil, 2025)
Reinforced concrete structures are susceptible to degradation in strength and stiffness when exposed to high temperatures during fire events. This degradation, which progresses linearly with increasing temperature and duration, can significantly compromise the structural integrity of buildings. The present study aims to evaluate the effectiveness of several post-fire repair techniques in restoring the mechanical performance of fire-damaged reinforced concrete beams. This research employs a systematic literature review approach, analysing experimental data from previous studies conducted by Hassan et al. (2018), Al-Nsour et al. (2023), and Kodur and Agrawal (2016). The primary materials and methods examined include Carbon Fibre Reinforced Polymer (CFRP), steel plates, and Basalt Fibre Reinforced Polymer Bars (BFRP-Bars), applied through various rehabilitation techniques such as Near Surface Mounted (NSM) and Reinforced Concrete Jacketing (RCJ). The evaluated data cover technical parameters such as specimen dimensions, thermal exposure scenarios (400 °C and 600 °C), exposure duration, and resulting changes in structural behaviour, including maximum load capacity, deflection, and residual deformation. The findings indicate that exposure to 600 °C for 120 minutes leads to strength degradation exceeding 60%. Post-fire rehabilitation using CFRP combined with steel plates restored the load capacity by up to 174,2% compared to the control specimen, while NSM application with BFRP bars increased capacity by 120,51%. Although deflection was relatively unaffected by thermal variations, both methods demonstrated high efficiency in restoring flexural performance. The study confirms that fibre-reinforced composite materials, when applied with proper techniques, are viable solutions for enhancing post-fire structural resilience.